PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN KOPERASI RUMAH BATIK SETU - Rasyid, Rosmita; Felice, Jeslyn (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Financial reports aim to provide information to users regarding the performance of the organization/company as well as the condition of the organization's/company's financial position including Micro, Small and Medium Enterprises (MSME) organizations. Financial reports can show management's performance in managing the organization and are useful for users in making decisions about their relationship with the organization. MSME managers often experience difficulties in compiling financial reports due to a lack of understanding and do not understand how to make accounting books in accordance with applicable standards, lack of outreach and lack of MSME accounting training. Partner in this community service activity (PKM) is a SME in the form of cooperatives that provide for the needs of their members. Financial reports are also needed by partner, namely the Setu batik house business cooperative to see the operating performance and financial position of this organization. This Setu batik house is under the auspices of the Setu batik house business cooperative. The location of Setu's batik house is in the Batan Indah complex, Setu District, South Tangerang. This organization records its operations in a very simple way. The financial reports that are made are simply Accountability Reports that are simple and cash-based. This partner's financial statements have not been prepared based on Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). For this reason, PKM is needed so that accounting understanding is the most dominant variable for the implementation of SAK EMKM to be applied. This PKM activity aims to assist partners in preparing financial reports based on SAK EMKM. Implementation of PKM is carried out by the method of compiling guidelines for preparing financial reports based on SAK EMKM, coordinating with partners by understanding financial reports prepared by partners and disseminating guidelines for preparing financial reports based on SAK EMKM so that PKM activities can be carried out properly and provide benefits for partners. Laporan keuangan bertujuan untuk memberikan informasi kepada pihak pengguna mengenai kinerja organisasi/perusahaan maupun kondisi posisi keuangan organisasi/perusahaan termasuk organisasi Usaha Mikro, Kecil dan Menengah (UMKM). Laporan keuangan dapat menunjukkan kinerja manajemen dalam mengelola organisasi dan bagi pemakai bermanfaat dalam mengambil keputusan tentang hubungannya dengan organisasi tersebut. Pengelola UMKM sering mengalami kesulitan dalam menyusun laporan keuangan karena kurangnya pemahaman dan tidak mengertinya membuat pembukuan akuntansi yang sesuai dengan standar yang berlaku, kurangnya sosialisasi dan belum adanya pelatihan akuntansi UMKM. Mitra dalam Pengabdian Kepada Masyarakat (PKM) ini adalah UMKM berupa koperasi yang menyediakan kebutuhan anggotanya. Laporan keuangan dibutuhkan pula oleh mitra yakni koperasi usaha rumah batik Setu untuk melihat kinerja operasi dan posisi keuangan organisasi ini. Rumah batik Setu ini dibawah naungan koperasi usaha rumah batik Setu. Lokasi rumah batik Setu berada di komplek Batan Indah Kecamatan Setu Tangerang Selatan. Organisasi ini melakukan catatan atas usahanya dengan cara yang masih sangat sederhana. Laporan keuangan yang dibuat hanyalah Laporan Pertanggungjawaban yang sederhana dan berbasiskan kas. Laporan keuangan mitra ini belum disusun berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah (SAK EMKM). Untuk itulah PKM ini diperlukan agar pemahaman akuntansi merupakan variabel yang paling dominan terhadap implementasi SAK EMKM dapat diterapkan. Kegiatan PKM ini bertujuan untuk membantu mitra dalam Menyusun laporan keuangan berdasarkan SAK EMKM. Pelaksanaan PKM dilakukan dengan metode menyusun panduan penyusunan laporan keuangan berdasarkan SAK EMKM, berkoordinasi dengan mitra dengan memahami laporan keuangan yang disusun mitra dan mensosialisasikan panduan penyusunan laporan keuangan berdasarkan SAK EMKM sehingga kegiatan PKM ini dapat terlasana dengan baik dan bemberikan manfaat bagi mitra.